Bild und Gegenbild - Brasilien im Werk Hugo Loetschers - Stooss-Herbertz, Adelaide; Stooss, Lucie (Contingentia, 2008)
Brazil is a popular writing subject. Its representation is full of varieties and reaches from "exotic country", "the land of the future", "paradise", "the unknown country" to a reputation of being underdeveloped with its inhabitants living in misery. Hugo Loetscher, an important contemporary Swiss writer, defined Brazil as a place of encounter with the enemy, i.e. another culture, nature or with himself: a discovery of the consequences of colonialism and the search for a new proper identity. This article focuses on the image of Brazil in Loetscher’s work, trying to get to know Brazil as a place in German literature that makes intercultural dialogue possible.